Biomarker characterization in endometrial cancer in Europe: first survey data analysis from 69 pathological academic and hospital labs - Santoro, Angela; Bragantini, Emma; Castiglione, Francesca; Ganesan, Raji; Matias-Guiu, Xavier; Frattini, Milo; Gallotta, Valerio; Garcia, Pablo; Pattni, Yatish; Tsiampali-Laprell, Julia; Brisaro, Brigitte; Barbareschi, Mattia; et al. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Introduction. Endometrial carcinoma (EC) is the commonest gynecological cancer affecting women in Western populations. To predict patient risk, the 2020 edition of the World Health Organization (WHO) Classification of Tumors of the Female Genital Tract stressed the importance of integrated histo-molecular classification of the disease. This survey analysis poses attention on the most frequently used immunohistochemical and molecular markers adopted in daily categorization of ECs in European laboratories.Methods. We analyzed data collected through questionnaires administered to 40 Italian, 20 Spanish, 3 Swiss and 6 United Kingdom (UK) laboratories. We collected information regarding daily practice in EC evaluation, specifically concerning mismatch repair status (MMR) and microsatellite instability (MSI). Summary and descriptive statistical analyses were carried out to evaluate the current practice of each laboratory.Results. The results show that MMR status is mainly evaluated by using immunohistochemistry (IHC) on most EC samples. The most frequent approach for the analysis of MMR status is IHC of four proteins (PMS2, MSH6, MSH2, MLH1). MSI analysis by molecular methods is uncommon but useful as a supplemental tool in specific conditions. MLH1 promoter hypermethylation and BRAF V600 mutations analysis are performed in case of negative expression of MLH1/PMS2. Other markers (mainly p53 followed by POLE and PTEN) are investigated in particular in Spain and Switzerland in a consistent number of cases.Conclusion. Guidelines consultation and standardization of laboratory procedures are efficient means for EC prognostic risk stratification and improving the quality of care.